Milrinone Dosing and a Culture of Caution in Clinical Practice. Issue 1 (January 2018) - Chong, Luke Yong Zheng; Satya, Kumar; Kim, Bernard; Berkowitz, Robert
Abstract : Milrinone is an invaluable agent in the treatment of end-stage heart failure patients who are refractory to optimal medical therapy. In addition to its use in acute decompensated heart failure, milrinone can also be employed as a home infusion therapy or a bridge to cardiac transplant. Concerns about its adverse effects, such as an increased risk of arrhythmias and hypotension, often limit the doses of milrinone used in clinical practice. In addition, milrinone is infrequently used or avoided entirely in patients with acute renal failure or end-stage renal disease because the drug is primarily cleared by renal excretion. Despite these concerns, studies that comprehensively reconcile the dose–response relationship and adverse events are scarce, and no clear provisions exist to guide milrinone dosing. After a brief discussion of the pharmacokinetics of milrinone, this article examines milrinone dosing, observed hemodynamic benefits, and documented adverse events across different studies. Abstract : Supplemental Digital Content is available in the text.